2019
DOI: 10.1186/s12885-019-5425-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Swainsonine represses glioma cell proliferation, migration and invasion by reduction of miR-92a expression

Abstract: BackgroundSwainsonine is a natural indolizidine alkaloid, its anti-tumor activity has been widely reported in varied cancers. This study aimed to investigate whether Swainsonine exerted anti-tumor impact on glioma cells, likewise uncovered the relative molecular mechanisms.MethodsAfter administration with diverse concentrations of Swainsonine, cell growth, migration and invasion in U251 and LN444 cells were appraised by the common-used CCK-8, BrdU, flow cytometry and Transwell assays. MiR-92a mimic, inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…Cyclin D1 and B1 promote the transformation of G1 → S phase and G2 → M phase in the cell cycle respectively. Decreasing the expression of cyclin D1 and B1 was related with the dysfunction of cell cycle transition and proliferation inhibition, like the BrdU + cells decreasing [ 46 , 47 ]. However, here, the decrease in the numbers of BrdU + and Ki67 + cells following 5-FU treatment was accompanied by a significant increase in the expression of both cyclin D1 and cyclin B1.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 and B1 promote the transformation of G1 → S phase and G2 → M phase in the cell cycle respectively. Decreasing the expression of cyclin D1 and B1 was related with the dysfunction of cell cycle transition and proliferation inhibition, like the BrdU + cells decreasing [ 46 , 47 ]. However, here, the decrease in the numbers of BrdU + and Ki67 + cells following 5-FU treatment was accompanied by a significant increase in the expression of both cyclin D1 and cyclin B1.…”
Section: Discussionmentioning
confidence: 99%
“…Piperlongumine (Figure 5) (125), swainsonine (Figure 5) (126), and sinomenine (Figure 5) (127) induce apoptosis and inhibit cancer cell growth through the PI3K/Akt/mTOR pathway, with decreased levels of p-Akt and p-mTOR, as evidenced by the results of Western blot analysis and immunofluorescence. Isoliensinine (Figure 5), matrine, dauricine (Figure 5), and cepharanthine (Figure 5) induce autophagy through the AMPK-TSC2-mTOR signaling pathway, with suppression of mTOR activity (128130).…”
Section: Alkaloidsmentioning
confidence: 96%
“…Subsequent studies explored the in vivo effects of SW on melanoma, 29 Ehrlich ascites carcinoma, 30 colorectal cancer, 31 human liver cancer, 32 lymphoma, 33 and leukemia 34 ; the results showed that all patients obtained good therapeutic effects 30,32,34,35 . The specific mechanisms of action include the following effects (Figure 3): inhibition of α‐mannosidase II, 137,138 promotion of tumor cell apoptosis, 139 enhancement of the immune system, 140 increase of intracellular calcium ion concentration, inactivation of the PI3K/AKT/mTOR signaling pathway, and repression of miR‐92a 141 . As a novel anticancer drug candidate, the biosynthesis of SW has also received attention as recently reviewed 142 …”
Section: Bioactivities Of Indolizidine Alkaloidsmentioning
confidence: 99%